A Comprehensive Investigation into the Relationship between Dietary Therapy Strategies for Metabolic Illnesses and the Underlying Myriad Factors - Kusmy, Prabin; Saxena Pal, Rashmi; Chaitanya, Motamari Venkata N. L.; Pal, Yogendra (Current Nutrition & Food Science, 2024)
Maintaining a well-balanced diet and considering how to fulfill all the adequate nutrition required by the body will help us live a healthy lifestyle. The risk of illness, infection, exhaustion, and poor performance increases when a balanced diet is absent. The anti-treatment technique of food modification has gained a lot of attention in research over the past few decades. Popular diets include Mediterranean, vegan, and low-carbohydrate diets. The vegan diet is a plant-based eating plan that eliminates animal products and emphasizes fruits, vegetables, legumes, whole grains, nuts, and seeds. The Palaeolithic age diet emphasizes eating full, unprocessed foods available to early people while avoiding grains, legumes, dairy products, refined sugar, and processed foods. Proponents claim it can improve health, and aid in weight loss. Numerous dietary patterns, such as caloric restriction (CR), dietary approaches to stop hypertension (DASH), ketogenic diets (KD), the Mediterranean diet (Medi), and Mediterranean-DASH diet Intervention for Neurological Delay (MIND) diet, have been tried to reduce body weight, any other disease infections, and cognitive decline. Increased Mediterranean diet adherence was linked to reductions in cardiovascular and neurological conditions, including Alzheimer's disease (AD) and related cognitive loss. The MIND diet, a new good dietary pattern has been linked to a significantly lower incidence of AD and slower rates of cognitive deterioration. The current piece of work emphasizes the introduction, nutritional components, and health advantages of different types of diet.
Keywords: calories